Functional, Anatomical, and Molecular Investigation of the Cardiac Conduction System and Arrhythmogenic Atrioventricular Ring Tissue in the Rat Heart. Issue 6 (19th December 2013) - Atkinson, Andrew J.; Logantha, Sunil Jit R. J.; Hao, Guoliang; Yanni, Joseph; Fedorenko, Olga; Sinha, Aditi; Gilbert, Stephen H.; Benson, Alan P.; Buckley, David L.; Anderson, Robert H.; Boyett, Mark R.; Dobrzynski, Halina
Abstract : Background: The cardiac conduction system consists of the sinus node, nodal extensions, atrioventricular (AV) node, penetrating bundle, bundle branches, and Purkinje fibers. Node‐like AV ring tissue also exists at the AV junctions, and the right and left rings unite at the retroaortic node. The study aims were to (1) construct a 3‐dimensional anatomical model of the AV rings and retroaortic node, (2) map electrical activation in the right ring and study its action potential characteristics, and (3) examine gene expression in the right ring and retroaortic node. Methods and Results: Three‐dimensional reconstruction (based on magnetic resonance imaging, histology, and immunohistochemistry) showed the extent and organization of the specialized tissues (eg, how the AV rings form the right and left nodal extensions into the AV node). Multiextracellular electrode array and microelectrode mapping of isolated right ring preparations revealed robust spontaneous activity with characteristic diastolic depolarization. Using laser microdissection gene expression measured at the mRNA level (using quantitative PCR) and protein level (using immunohistochemistry and Western blotting) showed that the right ring and retroaortic node, like the sinus node and AV node but, unlike ventricular muscle, had statistically significant higher expression of key transcription factors (including Tbx3, Msx2, and Id2) and ion channels (including HCN4, Cav 3.1, Cav 3.2, Kv 1.5, SK1, Kir 3.1, and Kir 3.4) and lower expression of other key ion channels (Nav 1.5 and Kir 2.1). Conclusions: The AV rings and retroaortic node possess gene expression profiles similar to that of the AV node. Ion channel expression and electrophysiological recordings show the AV rings could act as ectopic pacemakers and a source of atrial tachycardia.